Ploidy versus gender effects on inheritance of quantitative traits in Musa species - Oselebe, H.O.; Tenkouano, A. (2008)
Several factors including ploidy and genome composition influence the inheritance of agronomic traits in Musa populations. Research results have indicated that gender determines the inheritance of quantitative traits in this species, but whether inheritance patterns are ploidy-dependent or gender-dependent is not known. The present research is therefore aimed at evaluating the agronomic performance of progenies of 4x - 2x versus 2x - 4x crosses in Musa, in other to understand how gender or ploidy affect the inheritance of quantitative traits in interploidy crosses. The study was carried out at the High Rainfall Station of the International Institute for Tropical Agriculture (IITA), Onne in Southeastern Nigeria. Data on phenotypic performances of progenies of 4x - 2x and 2x - 4x crosses were collected for two seasons and analysed. The 4x - 2x crosses produced predominantly 3x progenies, whereas 2x - 4x crosses gave mostly 2x progenies. The diploid progenies of 2x - 4x crosses were shorter plants, took shorter time to flower and produced smaller bunches. The breeding values for the two groups were higher in the ratoon, than plant crop cycle. Complex microsporogenesis was observed in the parents of higher ploidy level (e.g. 4x) and may have resulted in production of predominantly monoploid gametes, n = 1x = 1C. Crosses between 4x and 2x parents, therefore, produced predominantly 3x progenies in 4x - 2x direction, but 2x progenies in 2x - 4x direction. Gender and ploidy determined the inheritance of characters in Musa, but with a preponderance of ploidy. The decision on the ploidy of individuals to serve as female or male parents in crosses is therefore critical.